2001
DOI: 10.1034/j.1600-0528.2001.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk group assessment of oral precancer attached to X‐ray lung‐screening examinations

Abstract: The mortality rate of oral tumours in Hungary, as in some other countries, is increasing. In order to assess risk groups for oral cancer and precancer, oral examinations were carried out as part of the X-ray screenings for lung cancer in the 3rd district of Budapest, Hungary. There were 5,034 adults who participated voluntarily in these investigations. After completing a questionnaire with 23 questions, a short oral examination was performed. Males comprised 57.7% of the group, and the age-distribution among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…A total of 16 OC/pre-cancer screening studies conducted in Europe over a span of three decades were retrieved from our searches (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The first of the screening programmes was conducted in 1973-1974 in Sweden (published in 1987 following a re-evaluation) and was the largest reported so far.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 16 OC/pre-cancer screening studies conducted in Europe over a span of three decades were retrieved from our searches (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The first of the screening programmes was conducted in 1973-1974 in Sweden (published in 1987 following a re-evaluation) and was the largest reported so far.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is similar to the prevalence reported in Brazilians (1.01%) ( 29 ), whereas this rate is much lower than that found in studies conducted in Slovenia (3.1%) ( 4 ) and Thailand (4.8%) ( 22 ). The prevalence of leukoplakia based on epidemiological data from different countries over the last 30 years varies from 1% to 13% with a mean value of 3% ( 30 ). Lichen planus was seen in 0.5% of our study population, a figure consistent with many previous studies ( 2 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…A Hungarian cross-sectional study performed during an oral screening program found that 3.7% of the individuals presented with PPOELs and that among these, 88% reported tobacco use. 18 In individuals residing in rural United States, smokeless tobacco was strongly associated with the presence of oral leukoplakia. 19 Individuals with tobacco-related lesions have an increased risk of OED.…”
Section: Likely Common Risk Factors Of Potentially Malignant Oral Mucmentioning
confidence: 99%